Birth stories of South African mothers of children with albinism: A critical human rights analysis - Sheryl Reimer-Kirkham; Barbara Astle; Jennifer Kromberg; Innocentia Mgijima-Konopi; Ramadimetja Shirley Mooa; Maretha de Waal; Meghann Buyco; Ikponwosa Ero; Dianah Msipa; Tintswalo Victoria Nesengani; Nomasonto Mazibuko; Ronell Leech; et al. (International Journal of Africa Nursing Sciences, 2024)
Background: The genetic condition of oculocutaneous albinism is disproportionately present in Africa. Little research has addressed the experiences of mothers impacted by albinism, even though they are more likely to be impacted by human rights violations. Methods: A qualitative study was designed to examine the resilience of mothers affected by albinism in South Africa. Virtual and in-person fieldwork was conducted with the facilitation of community-based researchers and local cultural liaisons. Findings: Giving birth to a child with albinism in South Africa, as in many parts of sub-Saharan Africa, was a life-defining moment for mothers and their families, setting them on a trajectory of health-related stigma, gender inequalities, reduced access to social determinants of health, and other human rights violations. Mothers engaged in sense-making processes shaped by the responses of birth attendants and families, and that reflected social discourses. Their resilience was impacted by access to health teaching, genetic counselling, and health and social services, which were often incomplete or absent all together. Civil society organizations, peer groups, and faith communities were vital in filling these gaps. Conclusions: The experience giving birth to a child with albinism was both the same and different compared to mothers forty years earlier. What varied was the digital availability of health information; progressive health and social policies and resourcing; and human rights instruments. These transformations point to best practices to support mothers’ resilience.